Rosetta Lander - Philae: Operations on comet 67P/Churyumov-Gerasimenko, analysis of wake-up activities and final state. (August 2017) - Ulamec, Stephan; O'Rourke, Laurence; Biele, Jens; Grieger, Björn; Andrés, Rafael; Lodiot, Sylvain; Muñoz, Pablo; Charpentier, Antoine; Mottola, Stefano; Knollenberg, Jörg; Knapmeyer, Martin; Kührt, Ekkehard; et al.
Abstract: The Lander Philae, part of the ESA Rosetta mission successfully landed on comet 67P/Churyumov- Gerasimenko on November 12th, 2014. After several (unplanned) bounces it performed a First Scientific Sequence (FSS), based on the energy stored in its on board batteries. All ten instruments of the payload aboard Philae have been operated at least once. Due to the fact that the final landing site was poorly illuminated, Philae went into hibernation on November 15th. Signals from the Lander were received again in June and July 2015, which indicated multiple awakening episodes of the lander. However, various attempts to re-establish reliable and stable communications links failed. Based on the analysis of the data gained during FSS, and during the contacts in June and July 2015 we draw conclusions on the state of Philae. In addition, images from the OSIRIS camera aboard the Rosetta Orbiter have allowed the identification of the exact position of Philae and its attitude, relative to the local surface terrain. This paper also gives an overview of the implications of Philae results for future engineering comet models, required particularly for the design of in-situ (landing) or sample return missions. Rosetta is an ESA mission with contributions from its member states and NASA. Rosetta's Philae Lander is provided by a consortium led by DLR, MPS, CNES and ASI with additional contributions from Hungary, UK, Finland, Ireland and Austria. Highlights: In this paper we give an overview of the search for the Rosetta Lander, Philae, after it went into hibernation. On-comet Lander measurements are set in context with Lander orientation as identified by OSIRIS imaging. Some lessons learned for future missions are listed.